Factors influencing job performance in Selangor’s construction industry - Bong, Chia Sin; Tan, Justin; Lim, Karen Qian Wei; Loi, Chiang Hong (2023)
A survey shows that Malaysia’s construction industry is grappling with a very significant issue where businesses in the sector have been losing money for a very long time. The performance of the employees is shown to have a negative impact on the performance of the organization, but it is unknown what factors exist in the construction business that have an impact on employee performance. Thus, this study aims to investigate the relationship between the independent variables (IVs) of work stress, work environment, job satisfaction, and organizational culture and the dependent variable (DV) of job performance among construction workers in Selangor, Malaysia. performance of Selangor, Malaysian, construction workers. Therefore, a deeper discussion of the connections between each IV and DV will be made in this study. In this study, 385 online questionnaires were given to Selangor’s top four construction firms. The Statistical Package for Social Sciences (SPSS) will be used to run the data collected from the respondents to get accurate results for analysis and interpretation. The link between DV and IV will also be shown using inferential techniques like multivariate regression analysis and Pearson’s correlation coefficient. In summary, the findings of this study show that there is no significant association between the work environment and the performance of construction employees, but there is a significant relationship between DV and three of the independent variables, including job satisfaction, work stress, and organizational culture. The main findings, their implications, limitations, and recommendations are discussed in this paper.